2021
DOI: 10.3389/fpsyg.2021.541510
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Post-traumatic Growth Among Healthcare Workers Who Experienced the Outbreak of MERS Virus in South Korea: A Mixed-Method Study

Abstract: Background: Infectious disease outbreaks such as COVID-19 and MERS pose a major threat to healthcare workers' (HCWs) physical and mental health. Studies exploring the positive changes gained from adapting to traumatic events, known as post-traumatic growth (PTG), have attracted much attention. However, it is unclear which factors or experiences lead to PTG among HCWs. The purpose of this mixed-method study was to investigate factors associated with PTG among HCWs who experienced the MERS outbreak in South Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
1
21
1
2
Order By: Relevance
“…Nevertheless, the results showed statistical differences across all PTG subscales except relation to others when comparing participants who experienced COVID-19 infection as opposed to those who did not, as shown in Table 2. In line with other studies (Lau et al, 2006;Bridgland et al, 2021;Huecker et al, 2021;Hyun et al, 2021); COVID-19 as severe acute respiratory syndrome appears to have been experienced as a harmful and traumatic stressful event by healthcare providers, eliciting post-traumatic stress responses. However, overcoming the trauma seems to lead them to constructive outcomes, underlining that PTG can occur after infectious diseases.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, the results showed statistical differences across all PTG subscales except relation to others when comparing participants who experienced COVID-19 infection as opposed to those who did not, as shown in Table 2. In line with other studies (Lau et al, 2006;Bridgland et al, 2021;Huecker et al, 2021;Hyun et al, 2021); COVID-19 as severe acute respiratory syndrome appears to have been experienced as a harmful and traumatic stressful event by healthcare providers, eliciting post-traumatic stress responses. However, overcoming the trauma seems to lead them to constructive outcomes, underlining that PTG can occur after infectious diseases.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the retrieved articles considered healthcare professionals as a sample, as the literature has extensively analyzed the impact of the sanitary emergency on these workers. Despite the negative mental effects, dealing with the COVID-19 pandemic has forced workers to develop resilience strategies, as during other outbreaks [ 17 ]. As already mentioned, resilience is generally defined as the ability to adapt and maintain adequate functioning despite adverse events and can be conceptualized as a trait, outcome or process [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The post-disaster mental health literature and trauma research have actually shown that adverse effects on psychological health do not always occur and that traumatic experiences can even lead to positive emotional states and growth [ 11 , 12 , 13 , 14 , 15 , 16 ]. Even after experiencing terrible events, the evidence suggests that people may experience some positive aspects, such as in the case of bereavement, rape, cancer, terrorism, natural disasters and even epidemics, as in the case of the MERS outbreak [ 14 , 15 , 16 , 17 ]. The ability to adapt to unpleasant situations and to recover quickly from trauma has been studied through the constructs of resilience, posttraumatic growth (PTG) and coping strategies [ 11 , 12 , 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations